Thin section photomicrographs of rock samples from Lodwar and its environs, Turkana County, Kenya - Tanui, F; Olago, D; Ouma, G; Kuria, Z (University of Oxford, 2024)
Ten of 69 rock samples collected during a comprehensive geological mapping exercise in Lodwar (Turkana County, Kenya) conducted in February and May 2018 were petrographically analyzed. Thin sections were prepared at the Department of Mines and Geology laboratory using standard mounting techniques. The thin sections underwent detailed petrographic analysis to characterize mineral composition, texture, and rock fabric. Quality control measures included careful preparation of samples to avoid contamination, adherence to standard procedures for mounting and polishing, and detailed microscopy observations to ensure accurate interpretation of mineralogical and textural properties in the rock samples.